2017
DOI: 10.4103/ijd.ijd_191_17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of terbinafine 500 mg once daily in patients with dermatophytosis

Abstract: Introduction:Dermatophytosis are the most common fungal infections globally. Terbinafine is considered to have good potency against dermatophytes, but resistance to terbinafine is on the rise.Objective:The objective of this study was to evaluate the efficacy and safety of terbinafine 500 mg given once daily in treatment of patients with superficial dermatophytosis.Materials and Methods:It was a retrospective questionnaire-based survey. Each doctor was given survey questionnaire booklet containing survey forms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 18 publications
3
53
0
Order By: Relevance
“…In this present study, the allylamin antifungal (Terbinafin) resistance is nearly comparable to Indian study and triazole antifungal (Fluconazole, Itraconazole) resistance is more or less similar to Dominique and Pramod. [8][9][10] The extent of the problem is variable and depends on the type of fungus, the type of antifungal agents and geographical location of hospital or study area.9 Mukharjee et al in 2003 first confirmed, the report of Terbinafin resistance in superficial fungal infection. 11 Majid et al in their study reported that at the end of 12 weeks there were only 43% enrolled cases which were able to maintain a long term clinical cure after 2 weeks of oral terbinafin 4 but our study showed that in 20.22% cases there was incomple cure and relapse after 2 months of completion of treatment for 01 month.…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, the allylamin antifungal (Terbinafin) resistance is nearly comparable to Indian study and triazole antifungal (Fluconazole, Itraconazole) resistance is more or less similar to Dominique and Pramod. [8][9][10] The extent of the problem is variable and depends on the type of fungus, the type of antifungal agents and geographical location of hospital or study area.9 Mukharjee et al in 2003 first confirmed, the report of Terbinafin resistance in superficial fungal infection. 11 Majid et al in their study reported that at the end of 12 weeks there were only 43% enrolled cases which were able to maintain a long term clinical cure after 2 weeks of oral terbinafin 4 but our study showed that in 20.22% cases there was incomple cure and relapse after 2 months of completion of treatment for 01 month.…”
Section: Discussionmentioning
confidence: 99%
“…Although the standard treatment recommendation for tinea corporis/cruris is TRB 250 mg once a day (OD) for 2 to 3 weeks, even lesser treatment durations have been reported to be successful (1)(2)(3). Recently, however, a number of reports have documented clinical failure of TRB treatment (4)(5)(6)(7)(8)(9). High MICs and mutations in the target enzyme, i.e., squalene epoxidase (SQLE), have also been demonstrated among Trichophyton spp.…”
mentioning
confidence: 99%
“…in recent reports (8)(9)(10)(11)(12). Consequently, the use of high TRB dosages, in treatment of dermatophytoses, is becoming common (6,13). However, it is important to emphasize that clinical breakpoints have not been defined for TRB in dermatophyt-oses and that the in vitro data cannot be directly applied to clinical situations.…”
mentioning
confidence: 99%
“…(4–7) High minimum inhibitory concentrations (MICs) and mutations in the target enzyme SQLE have been demonstrated in a few recent reports and the use of higher TRB dosages is becoming common. (6,813) However, clinical breakpoints have not been defined for TRB in dermatophytoses and the in vitro data cannot be directly applied to clinical situations.…”
Section: Introductionmentioning
confidence: 99%